Clinical Profile And Outcomes Of Total Thymectomy In Patients With Myasthenia Gravis: A Retrospective Descriptive Cohort Study From A Tertiary Care Centre Of Nepal - Jaiswal, Lokesh Shekher; Sarraf, Deependra Prasad; Jaiswal, Anshu; Neupane, Durga (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Myasthenia gravis is an autoimmune disorder of neuromuscular junction causing various degrees of voluntary muscle weakness and disability. Medical treatment consists of acetylcholinesterase inhibitors, immunosuppressants, immunoglobulins and plasmapheresis. Total thymectomy has been shown to provide significant clinical benefit. Here, we present our experience of total thymectomy in patients presenting with myasthenia gravis. Methods: A retrospective analysis of all patients undergoing total thymectomy via median sternotomy for myasthenia gravis with or without thymoma from January 2015 to December 2024 were done. The data were entered and analysed in MS- EXCEL 2007. Results: A total of 11 patients underwent total thymectomy. The male to female ratio was 1.2:1. The age ranged from 13 to 56 years with mean age of 33.5±12.7 years. All patients had positive tests for Acetylcholine receptor antibody. All patients were on pyridostigmine therapy and four (36.4%) patients were on steroid treatment for control of symptoms. Seven (63.6%) patients had thymoma preoperatively. All patients underwent surgery via median sternotomy. The median duration of follow up was 40 months (IQR 26-58). Complete remission was seen in four (36.4%) patients and significant clinical improvement with minimal pyridostigmine requirement in six (54.5%) patients. No patients required steroid treatment postoperatively. Histopathological examination of non-thymomatous MG patients showed thymus hyperplasia. Postoperative histopathological examination of patients having thymoma showed Masoka stage I in five (71.4%) and one (14.3%) each of stage IIB and IVA. Conclusions: Total thymectomy via median sternotomy is a safe procedure and provides significant clinical benefit in patients of myasthenia gravis with or without thymoma.